2003
DOI: 10.1889/1.1832233
|View full text |Cite
|
Sign up to set email alerts
|

13.3: A Novel Approach to Tiled Displays

Abstract: A novel approach to tiling is described in which an array of specially designed moulded light guides is used to form a magnified image of a standard AMLCD panel. These arrays can be tessellated to form visually uniform display surfaces of essentially unlimited size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Taking the viewing angle ITrans collar performance into account (see §3.2.2), this results in a wall plug power efficiency of 1.4Lm/W. This is a significant improvement over the previous demonstrator [1], which utilized a white LED backlight, yielding an efficiency of only 0.3Lm/W. Figure 4 shows a graph of luminance and contrast ratio as a function of viewing angle.…”
Section: Brightness and Efficiencymentioning
confidence: 96%
See 2 more Smart Citations
“…Taking the viewing angle ITrans collar performance into account (see §3.2.2), this results in a wall plug power efficiency of 1.4Lm/W. This is a significant improvement over the previous demonstrator [1], which utilized a white LED backlight, yielding an efficiency of only 0.3Lm/W. Figure 4 shows a graph of luminance and contrast ratio as a function of viewing angle.…”
Section: Brightness and Efficiencymentioning
confidence: 96%
“…The new mould produces a row of light guides in which the unique lateral displacement of each element within the row is moulded into the part, avoiding the need for post-forming in the plane of the row. This has led to a marked improvement in uniformity over the previous method [1] where the elements within a row were all post-formed from straight moulded parts. The current design consists of 204 guides in a single row, having a pitch of 1.485mm at the light input end and 1.695mm at the light output end.…”
Section: Mouldingmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative to the refractive optics element, a waveguide optics element was constructed by using molded optical fiber or fibers array [2,3]. The study showed impressive advance in viewing angle characteristics.…”
Section: Figurementioning
confidence: 99%